New record of Ferrisa dasylirii (Cockerell) (Hemiptera: Coccomorpha: Pseudococcidae) in Indonesia - Zarkani, Agustin; Apriyanto, Dwinardi; Turanli, Ferit; Kaydan, Mehmet Bora (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
The occurrence of mealybug species, Ferrisa dasylirii (Cockerell) (Hemiptera: Pseudococcidae) was first reported in Indonesia. It was found on Durio zibethinus Murray (Malvaceae), Gliricidia sepium (Jacq.) (Fabaceae), Hibiscus spp. (Malvaceae), Psidium guajava L. (Myrtaceae), Solanum torvum Swartz (Solanaceae), and Theobroma cacao L. (Malvaceae) at some regencies in Bengkulu Province, Southern Sumatra, Indonesia.